Formation of an organic film on an electrode via a suspension of redox-active droplets in acidic aqueous solution - Dusilo Katarzyna; Siwiec Aleksandra; Holdynski Marcin; Peljo Pekka; Opallo Marcin (Elsevier Inc., 2025)
Previous electrochemical studies of redox emulsions have been mainly performed in the context of electro-organic synthesis. More recently, this research has been oriented towards applications of emulsions in flow batteries. Such biphasic systems seem to provide a suitable environment for reactions at the liquid–liquid interface. Taking an emulsion consisting of microdroplets of decamethylferrocene solution in a hydrophobic ionic liquid/toluene mixture in acidic aqueous solution as an example, we have demonstrated that an electrochemical redox reaction involving the hydrophobic redox probe occurs at the glassy carbon electrode|organic liquid film interface. This reaction is followed by ion exchange between liquid phases. This effect is explained by the instability of the emulsion. A portion of the organic liquid stays on the electrode surface after transfer to a purely aqueous electrolyte and remains electroactive.